Statistical and machine learning approaches for identifying biomarker associations in respiratory diseases in a population-specific region - Alazmi, Meshari; AlGhadhban, Amer; Almalaq, Abdulaziz; Said, Kamaleldin B.; Faden, Yazeed (Frontiers in Artificial Intelligence, 2025)
The growing interest in utilizing clinical blood biomarkers for non-invasive diagnostics has transformed the approach to early detection and prognosis of respiratory diseases. Biomarker-driven diagnostics offer cost-effective, rapid, and scalable alternatives to traditional imaging and clinical assessments. In this study, we conducted a retrospective analysis of 913 patients from a local respiratory clinic in Hail region, evaluating the diagnostic relevance of 15 blood biomarkers across four respiratory conditions: COVID-19, pneumonia, asthma, and other complications. Through data-driven analysis, statistical correlation assessments, and machine learning classification models (decision tree classifiers), we identified significant biomarker interactions that contributed to disease differentiation. Notably, CRP and HGB demonstrated a strong negative correlation (−55%), supporting the well-established role of systemic inflammation in anemia of chronic disease. Additionally, Ferritin and LDH exhibited a positive correlation (+50%), indicating metabolic stress and cellular injury in severe respiratory illnesses. Other significant correlations included Creatinine and ESR being negatively associated with RBC, while GGT and ALT were positively correlated (+49%). Additionally, bilirubin and HGB were positively correlated (+49%), collectively reflecting systemic inflammatory and metabolic responses associated with respiratory pathology. The machine learning model demonstrated high predictive accuracy, with the following performance metrics: COVID-19: Precision (0.94), Recall (0.96), F1-score (0.95). Pneumonia: Precision (0.97), Recall (0.71), F1-score (0.85). Asthma: Precision (1.00), Recall (0.95), F1-score (0.97). Other Complications: Precision (0.88), Recall (0.90), F1-score (0.90). These findings validate the diagnostic potential of biomarker panels in respiratory disease classification, offering a novel approach to integrating statistical and computational modeling for clinical decision-making. By leveraging biomarker relationships and machine learning algorithms, this study contributes to the development of personalized, non-invasive, and cost-effective diagnostic tools for respiratory diseases, ultimately improving patient outcomes and healthcare efficiency.